Genetic variability analysis for various yield attributing traits in rice genotypes (Journal of the Bangladesh Agricultural University, 2017)
An experiment was conducted using a randomized complete block design to estimate genetic variability of ten rice genotypes. Analysis of variance for yield and yield contributing traits showed significant (p60%) along with high genetic advance and genetic advance as percentage of mean were found for all the traits indicating prevalence of additive gene action, which provides good scope for further improvement by selection.J. Bangladesh Agril. Univ. 15(1): 15-19, January 2017